KNOWLEDGE AND AWARENESS ON FAMILY PLANNING PRACTICE (CODE 1) AMONG THE HIGH RISK MOTHERS IN ONE LOCAL HEALTH CLINIC, IPOH, MALAYSIA - Pek YS (Asian Journal of Medicine & Health Sciences, 2019)
The proper use of contraceptive has significantly improved health-related outcomes among the mothers and infants.1,2 Each pregnancy and childbirth places a health risk for the mother and the risk is magnified if she is at high risk or with preexisting chronic medical conditions.3 Family planning programme has been implemented free or at affordable charges in Malaysia Healthcare System; however, it was underutilized or not being fully utilized.4 Based on the health records and returns from January till December 2016 in one local maternal-child health clinic, as high as 62.5% of registered high risk mothers were reluctant to practice family planning Code 1 (hormonal methods of contraceptive). High risk pregnancy cause complications for both mother and infant; also affecting the whole family system. Literatures suggest that health education has positive impacts in changing individual’s health behavior; also empowering the clients to take charge of their own health decisions and behavior.